WALMART'S GROCERY PICKUP ADVERTISING ICONOLOGY ANALYSIS - Hadi, Khaiqal; Prathisara, Gibbran; Wibowo, Arif Ardy (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
Walmart is one of the shopping companies in America that campaigned for their newest service, namely Walmart grocery pickup. A Grocery Pickup service so that every customer no longer needs to go from the vehicle to pick up food items that have been ordered previously. The advertising packaging is conceptualized in a unique way to attract the attention of its consumers successfully. This research wants to analyze the ad's ideology, which wants to know the basic idea of making the ad. Analyzing the ad, the researcher uses the main theory to consume the advertising with Gillian Dyer Iconology theory to determine its ideology. Gillian Dyer's iconology discussed the ad went through three stages of meaning: denotation, connotation, and ideology. The results showed that four ideologies were obtained, including social equality, excellent service, free and easy. It does not differentiate between the customer and the form of service, and of course, there is no additional cost for using this service in this service. Walmart created this service because it wanted to make it easier for its customers who didn't have much time to shop at their store because of their busy customer activity and had not had time to go shopping.